La construcción de la identidad lesbiana en el marco de familias heteronormativas en Lima Metropolitana - Cuba, Lucero (2019)
The present article analyzes how the family discourses shape the process of construction of the lesbian identity of young and adult women from Metropolitan Lima. From a qualitative methodology, deepened in the interpretative processes of construction of the own lesbian identity as well as of the discourses received by the family of origin. Through a theoretical sample, interviews were conducted in depth to nine young and adult lesbian women in order to perform a generational analysis. It was found that the construction of a lesbian identity implies a process of resignification of heteronormative discourses that establish the abjection of the lesbian subject, resignification that becomes possible due to the lesbian referents in the culture and, therefore, varies according to the cultural context of the time. In this process, the family intervenes, on the one hand, reproducing the heteronormativity and, in a second instance, restoring the heterosexual order through different discourses of rejection to the lesbian subject, like heterosexualization, expulsion from the home, aggression, among others. Being an exploratory study, the need to deepen the subject from different perspectives stands out.